Penerapan Teknologi Tepat Guna pada Pengolahan Limbah Rumah Tangga di Desa Sukajaya Kabupaten Bandung Barat - Elih Mulyana; I Wayan Ratnata; Wasimudin Surya Saputra; Neris Peri Ardiansyah (Jurnal Ilmiah Teknologi Infomasi Terapan, 2020)
This paper aims to describe the educational process of household waste management training by applying appropriate technology as part of human resources development in processing household waste. The participation of housewives and non-governmental organizations in this activity is part of increasing sensitivity to the environment to overcome the problem of household waste. The application of appropriate technology in processing household waste is a major part of the PKM (Community Service) activities of the Assisted Village, the technology of organic and inorganic waste chopping machines is used to produce semi-finished materials for compost and paving blocks, at that stage the technology is appropriate to provide added value in the process household waste treatment. The utilization of organic waste powder that is processed with EM4 produces solid compost, and inorganic waste can be processed as a base material for paving blocks. The results of the PKM in the Assisted Village have added value both in improving the quality of environmental cleanliness and increasing employment for the surrounding community in utilizing appropriate technology as a household waste processor.